Utilization of the stillage from bioethanol production on waste bread for lactic acid and biomass production - Đukić-Vuković Aleksandra; Mojović Ljiljana; Vukašinović-Sekulić Maja; Rakin Marica; Nikolić Svetlana; Pejin Jelena; Hao Jian (Journal on Processing and Energy in Agriculture, 2012)
Lactic acid is an important chemical for food industry and monomer for production of biodegradable polymers. Emerging technologies for sustainable fermentative production of food additives include the utilization of by-products and wastes as substrates. Problem of stillage disposal, as a by-product with significant ecological imprint, is not adequately solved in Serbia and its utilization as a substrate for fermentation could be a promising strategy. Lactobacillus rhamnosus ATCC 7469 was selected for evaluation of optimal inoculum and initial sugar concentration for effective lactic acid and biomass production. Under the selected conditions (5% of inoculum and 55 g L-1 of initial sugar concentration) lactic acid yield of 92.3%, volumetric productivity of 1.49 g L-1 h-1 and number of viable cells of 109 CFU ml-1 were achieved. High number of viable cells indicates that the fermentation media remained after lactic acid removal could be used as a high-quality animal feed.